Calculation and Design of a Combined Buckling and Bending Testing Equipment - Nguyen, Van Hieu; Le, Xuan Truong (Old Journal, 2018)
In this study, a new combined buckling and bending testing equipment is calculated and designed to perform both tests in a single apparatus. Buckling testing is carried out on various length struts which are pinned and clamped ends. Buckling loading is determined by the test with the maximum range of 500 N. Struts using for buckling test are aluminum alloy with 2 mm x 20 mm cross section in various lengths of 300 mm, 350 mm, 400 mm, 450 mm and 500 mm. Bending testing is carried out to examine the flexural rigidity of the struts. In bending test, the changeable supports are designed which can be fixed, pinned and rolled. Struts using for bending test are aluminum and steel alloys with 3 mm x 20 mm cross section in length of 600 mm. Bending load is in a range of 20 N. The whole equipment was then simulated in commercial software to investigate the designed structure. The obtained results show that the designed structure is met requirements for working load conditions.